Hyponatremia Induced by Amlodipine - Lissa Sabrina; Sidharta Salim (PT Kalbe Farma Tbk., 2023)
Introduction: Hyponatremia (<135 mmol/L) is one of the most common electrolyte disturbances in clinical practice. Correct treatment can prevent worse outcomes. A case of hyponatremia supposedly induced by amlodipine besylate was presented. Case: A 74 year-old male with lethargy and occasional nausea and admitted to having chronic hyponatremia in the past years. He’s been taking clopidogrel, simvastatin, and amlodipine besylate regularly since 7 years ago and had a history of coronary angioplasty 7 years ago. His lowest serum sodium level was 128 mmol/L even though he already took a 500 mg of sodium chlorine once daily. His serum sodium level never reached the normal range despite increasing salt intake and fluid restriction. Discontinuation of amlodipine besylate and change to nebivolol result in increased serum sodium level to 131 mmol/L. Conclusion: This case of hyponatremia may be induced by amlodipine. Pendahuluan: Hiponatremia (<135 mmol/L) adalah salah satu gangguan elektrolit yang paling umum dalam praktik klinis sehari-hari. Tata laksana yang tepat dapat mencegah prognosis lebih buruk. Laporan ini memaparkan kasus hiponatremia diduga disebabkan oleh amlodipine besylate. Kasus: Laki-laki berusia 74 tahun datang dengan lesu dan mual sesekali dan mengaku menderita hiponatremia kronis dalam beberapa tahun terakhir. Dia telah mengonsumsi clopidogrel, simvastatin, dan amlodipine besylate secara teratur sejak 7 tahun yang lalu dan memiliki riwayat angioplasti koroner 7 tahun yang lalu. Kadar natrium serum terendahnya adalah 128 mmol/L, meskipun sudah mengonsumsi kapsul natrium klorida 500 mg sekali sehari. Kadar natrium serumnya tidak pernah mencapai kisaran normal, meskipun asupan garam dan pembatasan cairan sudah ditingkatkan. Amlodipine besylate dihentikan dan diganti dengan nebivolol; setelah itu kadar natrium serum menjadi 131 mmol/L. Simpulan: Kasus hiponatremia ini mungkin diinduksi oleh amlodipine.